No-fault compensation for ventilator-dependent children: a reasonable settlement value for lifetime attendant care - Jenkins RC; Boelens BW; Aasheim KL; Gravenstein N (Dove Medical Press, 2016)
Randall C Jenkins,1–3 Brian W Boelens,1 Kari L Aasheim,1 Nikolaus Gravenstein4–5 1University of Florida Self-Insurance Program, 2University of Florida Healthcare Education Insurance Company, 3Department of Health Services Research, Management & Policy, College of Public Health and Health Professions, 4Department of Anesthesiology, 5Department of Neurosurgery, College of Medicine, University of Florida, Gainesville, FL, USA Abstract: Severe neurological outcomes sustained in childhood often result in lifetime health care needs that are beyond the financial means of most families. When severe neurological deficits are alleged to have resulted from professional negligence, relief may be sought through litigation; however, the American tort system often yields inconsistent results or no compensation for patients. We sought to identify a reasonable, objective, and data-based monetary range for a no-fault compensation system with high- and low-financial limits for those with severe neurological deficits. Based on documented life expectancies and attendant care cost studies, the data analysis indicates a no-fault settlement payment ranging from US$479,712.24 to $3,098,504.16, reasonably ensures care and services for life. Keywords: cost of health care, health law, health regulation, long-term care, medical malpractice